Severe early-onset manifestations of generalized arterial calcification of infancy (mimicking severe coarctation of the aorta) with ABCC6 gene variant — Case report and literature review - Fãgãrãşan, Amalia; Gozar, Liliana; Ghiragosian, Simina-Elena Rusu; Murariu, Mircea; Pop, Marian; Crauciuc, Andrei; Miclea, Diana; Şuteu, Carmen Corina (Frontiers in Cardiovascular Medicine, 2022)
Introduction Generalized arterial calcification of infancy (GACI) is a rare cause of infantile heart failure and systemic hypertension with a poor prognosis, characterized by extensive calcification and proliferation of the intimal layer of large and medium sized arteries. Case report We present the first case report of successful surgical treatment of severe aortic arch obstruction by calcified plaques mimicking severe coarctation of the aorta and the outcome (of bisphosphonate therapy) in a newborn with GACI. Furthermore, we report the identification of a variant in ATP Binding Cassette Subfamily C, Member 6 (ABCC6) gene, possibly associated with severe early-onset manifestations of GACI. Conclusion This case report highlights the importance of considering GACI in an infant with heart failure, systemic hypertension, and evidence of increased echogenicity of the arterial vessels. We noted the favorable outcome in improving the aortic calcification in our patient after surgical treatment and bisphosphonates therapy. Early diagnosis and treatment improve the long-term prognosis. A better understanding of this rare genetic disease could lead to new therapeutic strategies.